Development of Bamboozle Media for English Language Learning in Elementary School - Siti Hanifah Rizkiyah; Dayu Retno Puspita; Ferry Perdiansyah (International journal of technology and education research, 2025)
This research aims to develop an interactive learning media using Baamboodzle games for English subjects in the 3rd grade of SDN Pabuaran 2 Kota Tangerang. The research method applied is Research and Development (R&D) using Sugiyono’s development model, which includes potential and problem analysis, data collection, product design, design validation, design revision, product testing, and product revision. The results show that Baamboodzle media can enhance students' learning interest, activeness, and vocabulary comprehension in English. Expert validation in media and content stated that the product is feasible for use with minor revisions. This media is expected to be an innovative alternative for English learning in elementary schools.